2019
DOI: 10.1080/10615806.2019.1586888
|View full text |Cite
|
Sign up to set email alerts
|

Biased interpretation in perfectionistic concerns: an experimental investigation

Abstract: We present the computation of receiver noise temperature which includes the effects of mutual coupling of two different radio telescopes deployed in the Murchison Radioastronomy Observatory, namely the Murchison Widefield Array and the prototype Engineering Development Array. We used three different formulations that only require information of measured noise parameters of the low noise amplifier as used in the radio telescope and simulated S-parameter of the array to perform the calculation. In addition, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Un estudio mostró que cuando aumentan los síntomas de ansiedad, disminuye el afrontamiento flexible o viceversa (González Tovar & Hernández Rodríguez, 2021), esto es, peores estrategias de afrontamiento flexible mayor es la tasa de ansiedad (Howell et al, 2019). Esto se debe a que las medidas tomadas por las autoridades para controlar la pandemia (distanciamiento social, cuarentena, etc.)…”
Section: Ansiedad Y Afrontamiento Durante La Pandemia Por Covid-19unclassified
“…Un estudio mostró que cuando aumentan los síntomas de ansiedad, disminuye el afrontamiento flexible o viceversa (González Tovar & Hernández Rodríguez, 2021), esto es, peores estrategias de afrontamiento flexible mayor es la tasa de ansiedad (Howell et al, 2019). Esto se debe a que las medidas tomadas por las autoridades para controlar la pandemia (distanciamiento social, cuarentena, etc.)…”
Section: Ansiedad Y Afrontamiento Durante La Pandemia Por Covid-19unclassified
“…The work of Stoeber and colleagues supports the view that perfectionistic standards are associated with counter-productive behaviours that reduce task efficiency (Stoeber, 2011;Stoeber & Eysenck, 2008). Other experimental studies using attention and interpretation bias paradigms have also found support for the cognitive behavioural model of perfectionism (Howell et al, 2016(Howell et al, , 2019Tonta et al, 2019). Although not experimental analyses manipulating a single variable of interest, qualitative studies can also contribute to the understanding of maintaining mechanisms with a meta-synthesis indicating that self-worth dependent on achievement and cognitive-behavioural maintaining factors were consistent themes across 37 qualitative studies (Egan et al, 2022).…”
Section: Empirical Tests Of the Cognitive Behavioural Theorymentioning
confidence: 80%